An Ergonomic Office Interior Design Study on Improving Employee Performance and Job Satisfaction - Miska, Loudia; Azzahra, Salwa (International Journal Administration, Business & Organization, 2025)
The increasing complaints of employee fatigue, stress, and declining productivity caused by non-ergonomic office layouts have made the role of workplace interior design more critical in modern organizations. Responding to this phenomenon, this study aims to examine how ergonomics-based office interior design influences employee performance and job satisfaction. A Systematic Literature Review (SLR) approach was employed to analyze journal publications from 2020-2025 that discuss ergonomic workplace elements such as lighting, ventilation, spatial planning, and the use of ergonomic furniture. The findings show that ergonomic interior design increases productivity by improving focus, workflow efficiency, and physical comfort. Natural lighting, adequate ventilation, and structured workspace organization enhance concentration and reduce stress, while the use of adjustable tables and chairs helps prevent musculoskeletal disorders. From a psychological perspective, factors such as neutral colors, visual neatness, and dedicated rest areas contribute to motivation, emotional stability, and a sense of belonging at work. These results imply that ergonomic office interior design represents a strategic and high-value investment for organizations, not only for improving employee well-being and performance in the short term but also for strengthening job satisfaction, loyalty, and long-term organizational sustainability.